2019
DOI: 10.1088/1674-1056/ab38a5
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals interlayer potential of graphitic structures: From Lennard–Jones to Kolmogorov–Crespy and Lebedeva models

Abstract: The experimental knowledge on interlayer potential of graphenites is summarized and compared with computational results based on phenomenological models. Besides Lennard-Jones approximation, the Mie potential is discussed, Kolmogorov-Crespy model and equation of Lebedeva et al. An agreement is found between a set of reported physical properties of graphite (compressibility along c-axis under broad pressure range, Raman frequencies for bulk shear and breathing modes under pressure, layer binding energies), when… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Dependence of angular frequency on N, ω(N ), may be interpreted within a simple classical model [13] in which all layers of atoms separated by about 2.06 Å in Y-direction are treated as masses connected by springs. This approach was found useful in case of interpreting, for instance, Raman spectra in a few layers graphene [26], [27], [28]. We find that a solution to this mathematical problem proposed by Tan et al [27] may be used as a description of the observed ω(N ) dependence.…”
Section: Pressure Response Of Samplementioning
confidence: 84%
“…Dependence of angular frequency on N, ω(N ), may be interpreted within a simple classical model [13] in which all layers of atoms separated by about 2.06 Å in Y-direction are treated as masses connected by springs. This approach was found useful in case of interpreting, for instance, Raman spectra in a few layers graphene [26], [27], [28]. We find that a solution to this mathematical problem proposed by Tan et al [27] may be used as a description of the observed ω(N ) dependence.…”
Section: Pressure Response Of Samplementioning
confidence: 84%
“…The development of moirépatterns in 2D materials is fundamentally affected by this stacking dependence of the binding energy, which in turn cannot be captured by the simpler LJ model. 70 We adopt the z-normals simplification (KC-z), 69 and we set a KC cutoff radius of 14 Å. An assessment on the formation of stacking domains vis-a-vis the employed interlayer (LJ vs KC) potentials is provided in Supplementary Sections S11 and S12 and Figures S22−S24 The Au substrate is composed of two rigid (111)-oriented atomic layers.…”
Section: Methodsmentioning
confidence: 99%
“…C, A, λ, δ, C 2n , and z 0 are the fitting parameters obtained from ab initio and experimental data. Initially parametrized and well adopted for graphitic materials, [160][161][162] the KC potential has been recently extended to model systems such as h-BN and TMDCs. 159,[163][164][165][166] Righi et al have compared the variation of interaction energy of graphene bilayer with interlayer separation computed using different methods (see Figure 4b).…”
Section: Empirical Formulations For the Interlayer Interactions In La...mentioning
confidence: 99%
“…C, A, λ, δ, C2n, and 0.25emz0 are the fitting parameters obtained from ab initio and experimental data. Initially parametrized and well adopted for graphitic materials, 160–162 the KC potential has been recently extended to model systems such as h‐BN and TMDCs 159,163–166 . Righi et al .…”
Section: Empirical Formulations For the Interlayer Interactions In La...mentioning
confidence: 99%